Digital-Twin approach to predict the drag coefficient of random arrays of spheres suspended in Giesekus viscoelastic fluids - Loiro, Carina Luzia Melo Monteiro (2021)
Apresentação efetuada na 17th International Conference of Computational Methods in Sciences and Engineering (ICCMSE 2021), Greece, 2021